Late Roman handmade grog-tempered ware producing industries in South East Britain - Lyne, M. A. B., (Archaeopress archaeology., 2015)
This publication deals with the Late Roman handmade grog tempered ware industries of East Sussex, the Hampshire basin, East Kent and West Kent, presenting corpora for these various wares.